Food Cultures of Mexico: Recipes, Customs, and Issues - Hernández Rodríguez, Rafael (Global kitchen (Greenwood Press (Westport, Conn.)), 2021)
"This exciting volume brings to life the food culture of Mexico, detailing the development of the cuisine and providing practical information about ingredients and cooking techniques so that readers can replicate some of Mexico's most important traditional dishes"--
Keywords: Cooking / Regional & Ethnic / Central American & South American; Cooking / Regional & Ethnic / Mexican; Food habits; History / Latin America / Mexico; Mexico; Cooking, Mexican; Mexico; Social life and customs; dept.wll

Developing self-directed learning strategies through creative writing: Three case studies of snowball writing practice in a college Chinese language classroom - Tu, I. Ju (Thinking Skills and Creativity, 2021)
This study investigates three learners’ self-directed learning (SDL) strategies in a college beginner level Chinese language classroom. Using a focus group and interviews to explore how the students recognize their own learning strengths and weaknesses, what strategies they develop during the SDL process, their awareness of learning contexts while adopting SDL, and how they exercise their agencies for SDL. Findings suggest that technology fluency, the disconnection between learning goals and SDL strategies, and learners’ unawareness of their learning strengths affects individuals’ agency regarding SDL strategies. These findings suggest the need for further discussion of language teachers’ role in instructing SDL strategies, the role of technology, and the use of written corrective feedback. © 2021
Keywords: dept.wll; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection